INTENSIFICATION OF THERMAL PROCESSES IN HIGH-HEATING FURNACES ON EXAMPLE OF «BSW» BY ENRICHING AIR MIXTURE BY THE OXYGEN - S. M. Kabishov; I. A. Trusova; P. E. Ratnikov; D. V. Mendelev (Литьë и металлургия, 2012)
Assesses the efficiency of the use of excess oxygen produced by the oxygen-compressor station in order to reduce the flow of oxygen gas and specific consumption of fuel, for the conditions of JSC «BSW».